Organelle movement and apical accumulation of secretory vesicles in pollen tubes of Arabidopsis thaliana depend on class XI myosins. (15th November 2020) - Wang, Xingjuan; Sheng, Xiaojing; Tian, Xiulin; Zhang, Yu; Li, Yan
SUMMARY: F‐actin and myosin XI play important roles in plant organelle movement. A few myosin XI genes in the genome of Arabidopsis are mainly expressed in mature pollen, which suggests that they may play a crucial role in pollen germination and pollen tube tip growth. In this study, a genetic complementation assay was conducted in a myosin xi‐c ( myo11c1) myosin xi‐e ( myo11c2 ) double mutant, and fluorescence labeling combined with microscopic observation was applied. We found that myosin XI‐E (Myo11C2)‐green fluorescent protein (GFP) restored the slow pollen tube growth and seed deficiency phenotypes of the myo11c1 myo11c2 double mutant and Myo11C2‐GFP partially colocalized with mitochondria, peroxisomes and Golgi stacks. Furthermore, decreased mitochondrial movement and subapical accumulation were detected in myo11c1 myo11c2 double mutant pollen tubes. Fluorescence recovery after photobleaching experiments showed that the fluorescence recoveries of GFP‐RabA4d and AtPRK1‐GFP at the pollen tube tip of the myo11c1 myo11c2 double mutant were lower than those of the wild type were after photobleaching. These results suggest that Myo11C2 may be associated with mitochondria, peroxisomes and Golgi stacks, and play a crucial role in organelle movement and apical accumulation of secretory vesicles in pollen tubes of Arabidopsis thaliana . Significance Statement: The localization of myosin XI in pollen tube is not clear, and which subtype of myosin XI is correlated with mitochondrial and vesicle movement is unknown. In this study, we found that Myo11C2‐GFP was partially colocalized with mitochondria, peroxisomes and Golgi stacks, and the double deletion mutation of Myo11C1 and Myo11C2 affected the movement of mitochondria and the accumulation of secretory vesicles in the Arabidopsis pollen tube. These results suggest that Myo11C2 may play an important role in organelle movement and apical accumulation of secretory vesicles in pollen tubes.